Relationship between Helicobacter pylori and immune dermatosis - Xin-Yan ZHAO; Hong-Yu REN; Ai-Ping FENG (Yixue xinzhi zazhi)
Infection with Helicobacter pylori (Hp) can result in imbalance in the immune system in humans. The long-term interaction of immunity between host and bacteria leads to loss of the skin au-toantigen tolerance, leading some immunological dermatoses. The eradication of Hp has been shown to relieve symptoms in some chronic immune skin diseases, such as urticaria, rosacea, psoriasis and auto-immune bullous disease,. However the relationship between Hp infection and Behcet's disease, sclero-derma, alopecia areata and allergic purpura is still controversial. This review focuses on the relationship between Hp infection and common immune skin diseases.